(untitled) (Citizenship in Action: Extension and Culture Magazine, 2023)
The purpose of this article is to present how the activities of a university extension project, whose main objective is to produce resources and teaching materials for teaching Portuguese as a L2 language to deaf students, were adapted during the two years of the Covid-19 pandemic, a health situation that devastated social relations and, consequently, academic activities in Brazil and in the world. All project activities, previously planned for the face-to-face model, had to go through a reconfiguration process that would meet both the project’s demands and the technological possibilities available at that time. Positive and negative points were observed in the necessary adaptations. Finally, it was found that some adapted activities proved to be quite productive, and they can be maintained in the future planning of the project’s extension actions.